Non-Performing Loans and Banking Profitability - Ameur, Imane (Nieskuteczne pożyczki i rentowność banków, 2024)
Aim: This article aimed to determine the effect of macroeconomic and specific variables on the ratio of non-performing loans, and study the recursive direction of bank profitability to NPLs in Tunisian banks. Methodology: To formalise this phenomenon, the author proposed a panel data model that covers a sample of ten listed Tunisian banks over a period from 2007 to 2015. Findings: The empirical results indicate the determining power of bank profitability measured by asset profitability, solvency ratio, credit growth rate, provision-based debt coverage rate, bank size, inflation and unemployment. Implications: The effect of these variables veered between the preservative and destructive aspects of the quality of bank assets. Originality/value: This study enabled not only to identify the explanatory factors of this phenomenon, but also to verify the existence of a simultaneous relation between NPLs and bank profitability.
Financial Sciences. Nauki o Finansach, 2024, vol. 29, no. 1, s. 1-12
Keywords: non-performing loans; bank profitability; Tunisian banks; niewypłacalne pożyczki; rentowność banku; bank; Tunezja